Hubungan Self Efficacy dengan Tingkat Kecemasan Ibu Hamil Primigravida Trimester III - Faradisi, Himayatul Husna; Sugijati; Kiswati (Indonesian Journal Publisher, 2025)
Background: At the end of pregnancy, expectant mothers experience many changes, both physical and psychological. One of the various psychological aspects that often arises is worry about the upcoming birth. This factor is influenced by the level of self-efficacy, namely. Individual confidence in their abilities when facing difficulties Objective: The aim of this research is to find out whether there is a relationship between self-efficacy and anxiety levels in primigravida pregnant women in the third trimester who seek treatment at the Umbulsari Community Health Center. Method: The research method used a cross-sectional correlational design involving 28 participants where participants were taken purposively. The General Self-Efficacy Scale (GSES) was used in data collection in terms of assessing the level of self-efficacy as well as a questionnaire to measure the anxiety of primigravida pregnant women in the third trimester. Analysis using the Spearman Rank test showed a significant p-value of 0.000, indicating a strong relationship between the level of self-efficacy and the level of anxiety in this population. Results: The research results showed that the majority of participants had a moderate level of self-efficacy (53.6%) and a high level of worry (46.4%).Conclusion: pregnant women with high levels of self-efficacy tend to experience lower levels of worry. These findings highlight the importance of feeling confident about the birth process, which can help reduce levels of worry during this transformative period.